Use of Hydrocolloids in The Treatment of Phlebitis scores 2 and 3 in Siloam Hospitals Lippo Village Inpatient Room - Kristiningsih, Fransisca (PT. Nursing Genius Care, 2024)
The most frequently used invasive clinical procedure in hospitals is the insertion of a peripheral intravenous catheter for intravenous fluid administration access, where this procedure is susceptible to the risk of phlebitis complications. The incidence of Phlebitis is one of the indicators of the quality of nursing services that support patient safety at Siloam Hospitals Lippo Village. Research with the intervention of hydrocolloids in treating phlebitis wounds is the initiation of a wound care nurse, which aims to overcome the vascular response as measured by the respondents’ PIVA score and pain scale. This research is pre-experimental design with the one group pre and post-test design. The research was conducted at Siloam Hospitals Lippo Village. The sample in this study was 39 respondents who met the inclusion criteria: (1) respondents with Phlebitis (PIVAS score 2 or 3), (2) age ≥3 years, 3) willing to be a respondent and sign informed consent. Data processing was carried out by univariate and bivariate analysis (paired t-test on PIVAS scores and Wilcoxon signed rank test on the pain scale). PIVAS is a standardized phlebitis scale that is valid, reliable and clinically feasible. This study used PIVAS tools (Pheriperally Inserted Vascular Access Score tools) that modified Visual Infusion Phlebitis with a Kappa value of 0.826 with a significance value of 0.000 and a pain scale using the Numeric Rating Pain Scale (1-10). The results showed that the before and after the hydrocolloid intervention was significant in decreasing the PIVAS score (p-value 0.000) and pain scale (p-value 0.000). The PIVAS score had a correlation value of 0.934 (pre and post-test) with an average decrease of 1.974, while the pain scale decreased on the post-test measurement of 39 respondents. The results also showed that there was no difference in treatment before and after hydrocolloid intervention against the respondents’ age (p-value 0.725), respondents’ history of comorbidities (p-value 0.777) and phlebitis wound location (p-value 0.133). Hydrocolloid dressing has been shown to lower the PIVAS score and pain scale of respondents with phlebitis wounds, so it is recommended as a modern dressing option that applies to all age levels, comorbidities, and wherever the patient’s phlebitis wound is located